Stimulation of in vitro human skin collagenase expression by platelet-derived growth factor. - Bauer, E A (1985)
Platelet-derived growth factor (PDGF) is both chemoattractant and mitogenic for stromal cells. Here, we examined the effects of PDGF on collagenase expression by normal human skin fibroblasts. Culturing cells for 24 hr in the presence of PDGF at 0-180 ng/ml resulted in a dose-dependent, saturable increase in collagenase activity in the culture medium that was paralleled by equal increases in immunoreactive collagenase protein, suggesting enhanced synthesis of a catalytically unaltered enzyme. The specificity of this effect was demonstrated by comparing the collagenase-stimulatory effect with that on total protein synthesis and DNA synthesis. Under in vitro conditions that produced a 2.5-fold increase in collagenase synthesis, there was an approximately equal to 20% increase in total protein synthesis and no change in DNA synthesis. In addition, platelet factor 4, another platelet-derived protein, caused a less than 20% increase in collagenase expression. In time-course studies, stimulation of collagenase synthesis was first observed 8-10 hr after exposure to the growth factor. Conversely, when cells were primed with PDGF for approximately equal to 24 hr and the stimulator was then removed, an increased rate of synthesis was seen for an additional approximately equal to 6 hr, after which the rate reverted to control levels. Since the kinetic data suggested a possible pretranslational effect, fibroblasts cultured with PDGF were used to prepare mRNA. In cell-free translation, total protein synthesis was essentially unaltered; however, the growth factor caused a greater than 2-fold increase in translatable collagenase mRNA. The data suggest that PDGF specifically modulates collagenase synthesis, possibly through a series of events that lead to increased transcription or preferential translation of collagenase mRNA.